Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

e^x=-x+1, how do you solve this? @MIT 18.01 Single …

MIT 8.01 Physics I Classical Mechanics, Fall 1999
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
In this case x = 0 is the solution.
Normally with an expression e^(ax) = polynomial in x, numerical methods are needed. But with yours we can see a solution by inspection.
friend it is easy:just draw the graphs of y=e^x & y=-x+1....>the intersection point is the solution....this is a transcendental equation |dw:1320213287494:dw|

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

You may see http://www.wolframalpha.com/input/?i=solve%7Be%5Ex%3D-x%2B1%7D
Thanks....i jst give u a hint
mathematically take natural log on both sides e u will get point x where the solution exists
|dw:1321869467155:dw|
dif ratio x then Ln that result x=e^-1
hi! e^x=-x+1when dif it then e^x=-1 after Ln xLne=Ln-1 that result x=e^-1 ~ .36
|dw:1322221990014:dw||dw:1322222039311:dw|
The equation \[ e^x = -x + 1 \] has one and only solution, \( x = 1. \ \ \ x = e^{-1} \) is not a solution, something that is easily verifiable by substitution. (The uniqueness of the solution \( x = 1 \) can be proven by examining the function \( f(x) = e^x + x - 1. \ \ \ x = 1 \) is clearly a zero of f, but as \( f'(x) = e^x + 1 > 0 \) for all \(x\), it follows that it is also the only zero.)

Not the answer you are looking for?

Search for more explanations.

Ask your own question